2013
DOI: 10.1007/s00223-013-9699-5
|View full text |Cite
|
Sign up to set email alerts
|

Prevalence of Postmenopausal Osteoporosis in Italy and Validation of Decision Rules for Referring Women for Bone Densitometry

Abstract: We report the prevalence of osteoporosis, osteopenia, and fractures in a cohort of Italian women randomly recruited among the general population and validate the use of clinical guidelines in referring women for bone density testing. We enrolled in the study 995 healthy women (age range 45-92 years). A bone density test at the lumbar spine and femur was performed and a questionnaire on osteoporosis risk factors completed for all patients. The prevalence of osteoporosis was 33.67 %, that of osteopenia was 46.63… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
11
0
2

Year Published

2017
2017
2022
2022

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 17 publications
(14 citation statements)
references
References 42 publications
1
11
0
2
Order By: Relevance
“…Controls were recruited from the general population starting from the database used for our previous study, fully described elsewhere [ 27 ]. Briefly, controls were enrolled from the general practitioner lists amongst non-diabetic women without diseases active on bone metabolism, matched for age and BMI to T2DM patients, as previously described.…”
Section: Methodsmentioning
confidence: 99%
“…Controls were recruited from the general population starting from the database used for our previous study, fully described elsewhere [ 27 ]. Briefly, controls were enrolled from the general practitioner lists amongst non-diabetic women without diseases active on bone metabolism, matched for age and BMI to T2DM patients, as previously described.…”
Section: Methodsmentioning
confidence: 99%
“…Osteoporosis is a skeletal disease characterized by low bone mass, structural deterioration of bone tissue, and compromised bone strength predisposing to an increased risk of fracture. [ 1 , 2 ] It is one of the most common metabolic diseases and a leading cause of morbidity and mortality in the elderly. [ 3 ] Prior studies showed that several conditions, such as aging, sex, period of amenorrhea, parental history of fracture, [ 4 , 5 ] dietary calcium intake, vitamin D deficiency, low body mass index (BMI), [ 6 ] reduced physical activity, [ 7 ] and thyroid function [ 8 ] have been proposed as associated factors in bone mineral density changes in the elderly.…”
Section: Introductionmentioning
confidence: 99%
“…Osteoporosis is a skeletal disease characterized by low bone mass, structural deterioration of bone tissue, and increased susceptibility to bone fractures [1,2]. Osteoporosis is one of the most common metabolic bone disorders and a leading cause of morbidity and mortality in the elderly [3].…”
Section: Introductionmentioning
confidence: 99%